Tropical Soda Apple: Biology, Ecology and Management of a Noxious Weed in Florida - Brent Sellers; Jay Ferrell; J. Jeffrey Mullahey; Pat Hogue (EDIS, 2019)
Revised! SS-AGR-77, a 5-page illustrated fact sheet by Brent Sellers, Jay Ferrell, J. Jeffrey Mullahey, and Pat Hogue, informs readers about this serious weed problem in perennial grass pastures and native areas of Florida. It details the weed's taxonomy, biology, ecology, chemical control, biological control and management. Includes further sources of information. Published by the UF Department of Agronomy, February 2009.